Fatigue in multiple sclerosis: Associations with clinical, MRI and CSF parameters. (July 2018) - Biberacher, Viola; Schmidt, Paul; Selter, Rebecca C; Pernpeinter, Verena; Kowarik, Markus C; Knier, Benjamin; Buck, Dorothea; Hoshi, Muna-Miriam; Korn, Thomas; Berthele, Achim; Kirschke, Jan S; Zimmer, Claus; et al.
Background: Damage of different brain structures has been related to fatigue. Alternatively, functional alterations of central nervous system (CNS) cells by the inflammatory milieu within the CNS may be responsible for the development of fatigue. Aim: To investigate the effect of structural brain damage and inflammatory cerebrospinal fluid (CSF) changes on fatigue in multiple sclerosis (MS). Methods: We determined the association of different clinical, CSF and magnetic resonance imaging (MRI) parameters with prevalence and severity of fatigue, as measured by the Fatigue Scale for Motor and Cognitive Functions in 68 early MS patients (discovery cohort). We validated our findings in two MS cohorts: the MRI validation cohort ( N  = 233) for the clinical and MRI parameters, and the CSF validation cohort ( N  = 81) for the clinical and CSF parameters. Results: Fatigue was associated with clinical disability. Fatigue did not correlate with any CSF parameter but correlated negatively with total and cortical grey matter volume. However, when controlling for Expanded Disability Status Scale (EDSS) in a multivariate model, these associations lost significance. Conclusion: Disability and disease duration best explain fatigue severity but none of the tested MRI or CSF parameter was reliably associated with fatigue.